Causes and effects of global warming and ways to solve it (Al-Farooq Journal of Sciences, 2026)
This research includes a study of the phenomenon of global warming, its most important components and causes, the types of gases present in it , indicators of the occurrence of this phenomenon ,and the disasters resulting from it . And review some of the previous reports published by the British government on this subject . Global warming in Libya , which severely affects a significant  and the effects of global warming  in Libya and how to deal with this phenomenon, mentioning the factors that lead to alleviating this phenomenon, and the results were reached :-   1-    Reliance on renewable energy and electric and gas cars . 2-    Vegetation cover, increasing  afforestation in cities to soften the atmosphere and stabilize the soil.3-    Water management: protecting the man-made river, rehabilitating dams and improving the use of water resources. 4-    Adaptation to climate change, programs to protect coasts and cities from erosion and floods .5-    Policies and awareness, the necessity of effective government intervention .